Characterization of the TcDot1A and TcDot1B isoforms: Implication of H3K76 differential methylation during Trypanosoma cruzi life cycle - Balestrasse, Malena (2019)
Trypanosome cruzi, the ethiologic agent of Chagas Disease, affects a large number of the population in Latin America. It has a complex life cycle alternating between a mammalian host and the vector insect, Triatoma infestans. This cycle consists of three well-defined stages: amastigotes, epimastigotes and trypomastigotes. When the parasite faces different environments, it requires changes in gene expression in order to survive. Hence, gene expression regulation modulated by chromatin organization might be a key aspect to understand adaptation. Despite Trypanosomes gene expression is mainly regulated post transcriptionally, there are evidences that chromatin influence gene expression regulation. Recent studies have shown that homologues DOT1 methyltransferases, called DOT1a and DOT1b, are involved in the methylation of lysine 76 of histone H3 in T. cruzi. In T. brucei, DOT1a mediates H3K76 mono and di-methylation, whereas DOT1b also catalyzes H3K76 tri-methylation. However, these two enzymes remain poorly characterized.In this project, we intend to characterize the enzymatic activity and study the relevance of TcDOT1a and TcDOT1b during cell cycle and the metacytogenesis process. Therefore, to evaluate the catalytic activity using, we have successfully cloned and transformed a null DOT1 yeast strain with TcDOT1a. We are currently evaluating heterologous complementation. Simultaneously, we are working on TcDOT1b. Additionally, to analyze the isoforms subcelular location and their effects on cell cycle progression and differentiation, we have cloned the TcDOT1 isoforms in a pRibotex vector with an N-terminal HA-tag and transfected CL-Brener strain. Unfortunately, it resulted toxic for the cell. We are currently switching to use an inducible vector. Overall, our data will be useful to further understand the role of the DOT1 isoforms and the differential methylation of H3K76 in T. cruzi. In the long term, our findings might unravel new targets search for antiparasitic drugs.